C-reactive Protein Elevation Is Associated With QTc Interval Prolongation in Patients Hospitalized With COVID-19 - Isakadze, Nino; Engels, Marc C.; Beer, Dominik; McClellan, Rebecca; Yanek, Lisa R.; Mondaloo, Bahareh; Hays, Allison G.; Metkus, Thomas S.; Calkins, Hugh; Barth, Andreas S. (Frontiers in Cardiovascular Medicine, 2022)
Background The relationship between inflammation and corrected QT (QTc) interval prolongation is currently not well defined in patients with COVID-19. Objective This study aimed to assess the effect of marked interval changes in the inflammatory marker C-reactive protein (CRP) on QTc interval in patients hospitalized with COVID-19. Methods In this retrospective cohort study of hospitalized adult patients admitted with COVID-19 infection, we identified 85 patients who had markedly elevated CRP levels and serial measurements of an ECG and CRP during the same admission. We compared mean QTc interval duration, and other clinical and ECG characteristics between times when CRP values were high and low. We performed mixed-effects linear regression analysis to identify associations between CRP levels and QTc interval in univariable and adjusted models. Results Mean age was 58 ± 16 years, of which 39% were women, 41% were Black, and 25% were White. On average, the QTc interval calculated via the Bazett formula was 15 ms higher when the CRP values were “high” vs. “low” [447 ms (IQR 427–472 ms) and 432 ms (IQR 412–452 ms), respectively]. A 100 mg/L increase in CRP was associated with a 1.5 ms increase in QTc interval [β coefficient 0.15, 95% CI (0.06–0.24). In a fully adjusted model for sociodemographic, ECG, and clinical factors, the association remained significant (β coefficient 0.14, 95% CI 0.05–0.23). Conclusion An interval QTc interval prolongation is observed with a marked elevation in CRP levels in patients with COVID-19.